A Novel Method for 57Ni and 57Co Production using Cyclotron-Generated Secondary Neutrons - H. Suryanto; I. Kambali (PPIKSN-BATAN, 2018)
57Ni and 57Co radioisotpes are used in the synthesis of radiopharmaceuticals, for research purposes, as well as radiotherapy in nuclear medicine due to its decay characteristics. In this research, 57Ni and 57Co were produced using secondary neutrons. The secondary neutrons employed in this investigationwere generated by bombarding 11 MeV protons intoa target system consisting of HavarÒ foil as a vacuum window, aluminum foil as an energy degrader, aluminum tube as a target holder and nickel foil as a target via (p,n), (n,n) and (n,2n) nuclear reactions. The TALYS-calculated data were used to understand the origin of the secondary neutrons. In this experiment, variable Ni target thicknesses of 75, 150 and 225 mm were irradiated with a fixed proton beam dose of 0.67 mAhr in order to study the dependence of the radioisotope yields on the target thickness. For the first time, 57Ni and 57Co radioisotopes wereproduced and observed experimentally following 58Ni(n,2n)57Ni → 57Co nuclear reaction. Experimental results indicated that for 225-mm thick Ni target, the 57Ni yield of 10.85 ± 3.29 mCi/mAhr and 57Co yield of 6.04 ± 2.45mCi/mAhr were recorded after an hour cooling period. The resulted yieldsdid not strongly depend on the target thickness. This proposed novel method is a promising method to obtain higher radioactivity yield in the production of 57Ni and 57Co radioisotopes.